Flow states in exercise: A systematic review - Jackman, P. C.; Hawkins, R. M.; Crust, L.; Swann, C. (Psychology of Sport and Exercise, 2019)
Objectives: The purpose of this study was to systematically identify, review, synthesise, and appraise current literature on flow in exercise. By doing so, this study aimed to highlight gaps and future research directions that will help to advance understanding and application of flow states in this setting. Design: A systematic review using PRISMA guidelines. Methods: Eight electronic databases were searched in February 2019. Inclusion criteria were peer-reviewed studies focused on the investigation of flow in exercise. Exclusion criteria were studies that did not exclusively include exercise participants, or that focused on instrument development and/or validation. Data from included studies were extracted and reported in a narrative synthesis. Results: A total of 26 studies that were conducted with 4478 participants met the inclusion criteria. Several issues with the conceptualisation and measurement of flow in exercise were identified, which makes it difficult to draw meaningful conclusions about this literature. Nevertheless, there is tentative evidence that exergame design features, music, and virtual stimuli can affect at least some dimensions of flow. While little attention has been directed towards developing an explanatory theory, initial findings concerning the contexts and process underlying flow occurrence could offer a potential avenue for progress. Conclusions: The review advances knowledge by synthesising quantitative and qualitative evidence on flow states in exercise. By doing so, the review also highlights a range of conceptual and methodological issues in the field. Recommendations to address these issues and suggestions for making meaningful progress to develop understanding of flow states in exercise are advanced.